Regional Public Policy and Human Rights Based on Muhammad Natsir's Perspective in Kuantan Singingi - Fajar Illahi (Tanfizi : Journal of Islamic Constitutional and Political Law, 2026)
This study examines regional public policy and human rights from the perspective of Muhammad Natsir, focusing on policy implementation in Kuantan Singingi Regency, Indonesia. It investigates whether local government policies embody the principles of justice, public welfare, and human dignity emphasized in Natsir’s Islamic political thought. This research employs an empirical legal approach using qualitative methods. Primary data were obtained through interviews with local government officials, religious leaders, community representatives, and academics, supported by observations and analysis of regional regulations and policy documents. The findings reveal that regional public policies have improved public services and community participation but continue to face challenges related to equal access to services, protection of minority rights, and institutional accountability. From Muhammad Natsir’s perspective, public policy should integrate justice, moral responsibility, and respect for fundamental human rights as essential elements of governance. The study further demonstrates that effective rights-based policies require transparent decision-making, ethical leadership, and active public participation alongside compliance with legal norms. Strengthening coordination between local government institutions and civil society is necessary to ensure that regional policies consistently uphold constitutional values and human rights while reflecting Islamic ethical principles. This study contributes to the discourse on regional governance by demonstrating the contemporary relevance of Muhammad Natsir’s political thought in promoting human rights-oriented public policy and providing a normative foundation for developing accountable, inclusive, and socially just local governance.